Concise Review: Pluripotent Stem Cell‐Derived Cardiac Cells, A Promising Cell Source for Therapy of Heart Failure: Where Do We Stand?. (16th September 2015) - Gouadon, Elodie; Moore‐Morris, Thomas; Smit, Nicoline W.; Chatenoud, Lucienne; Coronel, Ruben; Harding, Sian E.; Jourdon, Philippe; Lambert, Virginie; Rucker‐Martin, Catherine; Pucéat, Michel
Abstract: Heart failure is still a major cause of hospitalization and mortality in developed countries. Many clinical trials have tested the use of multipotent stem cells as a cardiac regenerative medicine. The benefit for the patients of this therapeutic intervention has remained limited. Herein, we review the pluripotent stem cells as a cell source for cardiac regeneration. We more specifically address the various challenges of this cell therapy approach. We question the cell delivery systems, the immune tolerance of allogenic cells, the potential proarrhythmic effects, various drug mediated interventions to facilitate cell grafting and, finally, we describe the pathological conditions that may benefit from such an innovative approach. As members of a transatlantic consortium of excellence of basic science researchers and clinicians, we propose some guidelines to be applied to cell types and modes of delivery in order to translate pluripotent stem cell cardiac derivatives into safe and effective clinical trials. Stem Cells 2016;34:34–43